KEBIASAAN MAKAN IKAN LAYUR (Lepturacanthus savala) DI PERAIRAN DESA SUAK INDRAPURI KECAMATAN JOHAN PAHLAWANN KABUPATEN ACEH BARAT - Muhammad Arif Nasution; Mahendra Mahendra; Suprizal Suprizal (JURNAL PERIKANAN TROPIS, 2018)
This study aimed to determine feeding habits layur fish and composition of food eaten by layur. The study was conducted in september to october 2016. The method used in this research is survey method. The result showed that the types food of layur are small shrimp with a percentage value of 35%, then a small fish with a value of 17% and pulverized fish with a value of 48%. Frequency of occurrence type food obtained is 44% pulverized fish, small shrimp 37% and the lowest percentage of appearance food is small fish by 19%. IP value of small shrimp at 35% and the lowest part small fish by 9%, and then RLG of layur acquired intestinal length relative 0.91, intestinal length 32 and total length of 35 cm. Based on the value of RLG is less than 1, then the layur (Lepturacanthus savala) is a carnivorous (carnivores).